Impact of paravertebral block on perioperative neurocognitive disorder: a systematic review and meta-analysis of randomized controlled trials - Wang, Lu; Wang, Fei; Kang, Wanli; Gao, Guangkuo; Liu, Tao; Chen, Bin; Liu, Wei (Frontiers in Aging Neuroscience, 2023)
Objective: To investigate whether paravertebral block reduces postoperative delirium (POD)/delayed neurocognitive recovery (DNR) in adults after major surgery with general anesthesia. Methods: For this systematic review and meta-analysis, we searched online databases PubMed, EMBASE, CENTRAL, and Web of Science till March 19th, 2023 to examine studies which use paravertebral block (PVB) for perioperative neurocognitive disorder. Primary and secondary outcomes were identified for the incidence of perioperative neurocognitive disorder. We did not restrict the follow-up duration of the included studies. Statistical analysis was performed to calculate mean difference (MD), Odd ratios (OR) and CI between RCTs. The quality of the evidence was assessed with the Cochrane risk of bias tool. The registration number of the study in PROSPERO is CRD42023409502. PROSPERO is an international database of prospectively registered systematic reviews. Registration provides transparency in the review process and it helps counter publication bias. Results: Total 1225 patients from 9 RCTs were analyzed. The incidence of POD [Odds Ratio (OR) = 0.48, 95% CI 0.32, 0.72; p = 0.0004; I2 = 0%] and DNR [OR = 0.32, 95% CI 0.13, 0.80; p = 0.01; I2 = 0%] were significantly reduced in PVB group. The analysis showed no significant differences in postoperative MMSE scores [MD = 0.50, 95% CI -2.14, 3.15; p = 0.71; I2 = 98%]. Paravertebral block analgesia reduces pain scores and/or opioid use after surgery. Additionally, blood pressure was significantly lower in the PVB group, intraoperatively [MD = -15.50, 95% CI -20.71, -10.28; p < 0.001; I2 = 12%] and postoperatively [MD = -5.34, 95% CI -10.65, -0.03 p =0.05; I2 = 36%]. Finally, PVB group had significantly shorter hospital stays [MD = -0.86, 95% CI -1.13, -0.59; p < 0.001; I2 = 0%]. Conclusions: Paravertebral block analgesia may prevent perioperative POD/DNR in patients undergoing major surgery. Further research with large sample sizes is required to confirm its effectiveness.